Hubungan antara Kebiasaan Merokok dengan Kejadian Hipertensi di RSD dr. Soebandi Jember (Correlation Between Smoking and the Incidence of Hypertension in Department of Cardiovascular Disease RSD dr. Soebandi Jember) - Cici Eirmawati; Wiratmo Wiratmo; Prihwanto Budi S (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Hypertension is one of the non-communicable diseases that becoming a very serious health problems at this time. In Indonesia, approximately 6.8% of the causes of death at all ages due to hypertension. Smoking is one of the risk factor of hypertension. The purpose of this study is to determine correlation between smoking and the incidence of hypertension. The method of this research was a case control study. The sampling technique was the lottery technique. This research was conducted in Department of Cardiovascular Disease RSD dr. Soebandi Jember on May 9 to June 9, 2014 with 44 case respondents and 88 control respondents. The data was analyzed using logistic regression. The test results showed that smoking have a significant association with hypertension; 1) Correlation between smoking and hypertension (Sig. = 0.000; OR = 6.429); 2) Correlation between the number of cigarettes smoked and hypertension (Sig. = 0.000; OR = 2.490); 3) Correlation between the type of cigarettes smoked and hypertension (Sig. = 0.000; OR = 3.519); 4) Correlation between the duration of smoking and hypertension (Sig. = 0.000; OR = 2.902). As a conclusion, there is a correlation between smoking and the incidence of hypertension in men aged 30-60 years in Department of Cardiovascular Disease RSD dr. Soebandi Jember. Keywords: hypertension, smoking, number of cigarettes, type of cigarettes, duration of smoking